ANALISIS PENGUASAAN PASAR PADA PELAYANAN JASA BONGKAR MUAT PETIKEMAS OLEH PT. PELINDO III DI PELABUHAN L. SAY MAUMERE - Triana Rahmatika Putri; Siti Anisah (Fakultas Hukum, Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2021)
This study aims to determine the fulfillment of the elements of Article 19 letters a and b of Law No. 5 Year 1999 related to market control carried out by PT Pelindo III. Control of the market in the world of trading is not prohibited, it becomes prohibited if the business actor's behavior is in the sale of goods or services with the aim of killing competitors. In the Decision No. 15/KPPU-L/2018, the Commission Council only stipulated Article 17 paragraph (1) and (2) letter b of Law No. 5 Year 1999 regarding the monopoly carried out by PT Pelindo III. The Commission Council considers that the 100% mandatory stack policy stipulated by PT Pelindo III is not yet feasible to be established at a port that is multipurpose like a container port, especially with the additional logistics costs that are passed on to consumers, this results in losses for various parties. This research is a normative study using a conceptual, a statutory, and a case approach. The research show that it can be concluded that the consideration of the Commission Council in the decision on the actions committed by PT Pelindo III in the case is not in accordance with the rule of reason approach, the action refers to Article 19 letters a and b of Law No. 5 of 1999 which has been proven by considering an economic point of view, seeing the existence of witness evidence, expert testimony, and the Regulation of the Minister of Transportation which was violated by PT Pelindo III.